The level of homophobia in academic personnel at a university in istanbul and its affecting factors,İstanbul’da bir üniversitede akademik personelin homofobi düzeyi ve etkileyen faktörler - LÜLECİ, NİMET EMEL (My University, 2020)
ABSTRACT Objective: The aim of this study was to determine the levels of homophobic attitudes and related factors among senior students at a university in Turkey. Methods: The descriptive study sample consisted of 317 senior undergraduate students who met the inclusion criteria and accepted to participate in the study between March 20 and April 24, 2017. The study data were collected using the \"Personal Information Form\" to determine the socio-demographic characteristics of the students and \"Hudson-Ricketts Index of Homophobia\" to determine their homophobic attitudes. Descriptive statistics, the independent samples t-test (Student’s t-test) for the comparison of two groups and the one-way ANOVA test for the comparison of the means of more than two groups were used in the analysis of the data. Results: In the study, it was determined that 156 (49.2%) students had low levels homophobic attitudes and 148 (46.7%) students had high levels homophobic attitudes. In addition, it was found that 13 (4.1%) students got 87 points and had neutral level homophobic attitudes. Among the students who participated in the study. it was found that the homophobic attitude levels of the students who were women and who had individuals with different sexual orientation in their social environment were found to be lower (p<0.05). Conclusion: In this study, it was determined that university students have homophobic attitudes and the factors affecting homophobic attitudes of university students are gender and having different sexual orientation in the social environment. Keywords: Homophobia, homophobic attitudes, homosexuality, university students, factors
Keywords: Sağlık Bilimleri; Health Sciences; Klinik Tıp (MED); Clinical Medicine (MED)